Ernährung und Komplementärmedizin: Beratungsbedarf von Patienten = Diet and complementary medicine : Patient needs for consultation - Gschwendtner, Kathrin M.; Weis, Joachim (Der Onkologe, 2016)
Background and objectivesCancer patients and cancer survivors have a high demand for information about nutrition, diets and supplementation. The term complementary and alternative medicine includes some but not all of these approaches. This results in the question whether patients differentiate between these approaches and if this has any significance for counseling of cancer patients.Material and methodsFor this purpose a selective literature search was conducted. In addition, own study results are presented.ResultsThe boundaries between nutrition, cancer diets and supplements are flexible. It can be concluded that a consultation regarding these approaches can follow the recommendations for consultation about complementary and alternative medicine.ConclusionA consultation on complementary and alternative medicine is not easy due to the lack of evidence and diversity of approaches. The expected benefit to the patient as well as the safety of the approach should be taken into account in the decision-making process. Also the needs and subjective disease theory should be considered.
Gesehen am 25.11.2019